Leadership matters in the education of students with special needs in the 21st century - Obiakor, Festus E.; Banks, Tachelle; Rotatori, Anthony F.; Utley, Cheryl A. (Contemporary perspectives in special education., 2017)
This book provides a practical focus and framework for establishing insightful leadership that will enhance the learning of students with exceptionalities in the 21st century by discussing critical leadership dimensions and topics by leading academics. Topics discussed include the following: shifting leadership paradigms for all students in general and special education, district leadership strategies for implementing individualized academic and behavioral student interventions, preparing leaders to work with students with diverse learning needs, critical leadership roles for regular classroom teachers in educating learners with special needs, innovative leadership to increase school completion and graduation of general and special education learners, why psychologists need to be a part of the school leadership team, the importance of culturally responsive leadership in general and special education, the role of school leaders in helping learners with physical and health impairments, school leadership for all students in rural schools, the use of technology by leaders to improve special education services, an international example model of leadership in general and special education, and future perspectives of leadership in special education.Leadership Matters in the Education of Students with Special Needs in the 21st Century is a critically needed addition to the successful education of students with exceptionalities as it provides much needed and innovative leadership perspectives for effective instructional practices for today's students with special needs. The book can be a model for best practices for school district leadership teams challenged by the multifaceted needs of students with exceptionalities.